121k views
1 vote
Help me out Wishing! Solve the following: (x+3)(x+1)

User JustAGuy
by
5.5k points

2 Answers

3 votes

Answer:


{x}^(2) + 4x + 3 \\ solution \\ (x + 3)(x + 1) \\ = x(x + 1) + 3(x + 1) \\ = {x}^(2) + x + 3x + 3 \\ = {x}^(2) + 4x + 3

hope this helps...

Good luck on your assignment....

User Simmons
by
5.4k points
2 votes

Answer:


x^2+4x+3

Explanation:


(x+3)(x+1)= \\\\(x)(x)+(x)(1)+(3)(x)+(3)(1)= \\\\x^2+x+3x+3= \\\\x^2+4x+3

Hope this helps!

User Son Of A Beach
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.